2023
DOI: 10.1126/science.adf5307
|View full text |Cite
|
Sign up to set email alerts
|

A magnified compact galaxy at redshift 9.51 with strong nebular emission lines

Abstract: Ultraviolet light from early galaxies is thought to have ionized gas in the intergalactic medium. However, there are few observational constraints on this epoch, due to the faintness of those galaxies and the redshift of their optical light into the infrared. We report the observation, in James Webb Space Telescope (JWST) imaging, of a distant galaxy that is magnified by gravitational lensing. JWST spectroscopy of the galaxy, at rest-frame optical wavelengths, detects strong nebular emission lines due to oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 79 publications
1
55
0
Order By: Relevance
“…In addition to detailed investigations of remarkable individual NIRSpec spectra at high redshift (e.g., Williams et al 2023;Bunker et al 2023;Curti et al 2023), JWST spectra are also starting to be used for analysis of the chemical abundances of samples of distant galaxies. Matthee et al (2022) present NIRCam grism observations of [O III]/Hβ in concert with stellar mass estimates for a sample of 117 [O III]-emitting galaxies at 5.3 z 6.9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to detailed investigations of remarkable individual NIRSpec spectra at high redshift (e.g., Williams et al 2023;Bunker et al 2023;Curti et al 2023), JWST spectra are also starting to be used for analysis of the chemical abundances of samples of distant galaxies. Matthee et al (2022) present NIRCam grism observations of [O III]/Hβ in concert with stellar mass estimates for a sample of 117 [O III]-emitting galaxies at 5.3 z 6.9.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent remarkable NIRSpec spectra have revealed the rest-optical nebular properties of individual galaxies at z = 9.5 (Williams et al 2023) and, now, z = 10.6 (Bunker et al 2023). The low metallicities of the z > 8 targets observed by JWST, given their stellar masses and SFRs, suggest that they do not fall on the FMR that describes galaxies at z 3 (Langeroodi et al 2022;Williams et al 2023;Curti et al 2023). However, it is challenging to draw broad conclusions from such a small sample, which may or may not be representative of the full population at these redshifts, and questions remain about which calibrations can be used to accurately infer metallicity at such high redshifts.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We find a remarkably small size of r 30 hl 5 7 =  pc for MACS0417-z5BBG, where r hl is the half-light radius, and a best-fitting Sérsic index of ∼8, which is consistent with a compact bulge morphology. While new results on rest-UV sizes at z ∼ 5 with JWST are sparse, this size is much smaller than average sizes reported for galaxies at z  7 (e.g., Ono et al 2022;Yang et al 2022) but similar to some of the single-object discoveries found so far (e.g., Williams et al 2023).…”
Section: Sizementioning
confidence: 41%
“…Figure5presents the SFR-M star relation. For comparison, we show the main sequence estimated at z = 2, and z = 6(Iyer et al 2018), recent JWST results for the sources spectroscopically confirmed at z = 7 − 13 (Curtis-Lake et al 2023;Heintz et al 2022;Roberts-Borsani et al 2022;Robertson et al 2023;Tacchella et al 2023;Williams et al 2023), the HSTselected, brighter LBGs (M UV ; − 21.5) spectrosopically confirmed at z = 8 − 9 in CEERS(R.Larson et al 2023, in preparation), and the 16th-84th percentile of the distribution of simulated galaxies at z = 7 − 8(Behroozi et al 2019(Behroozi et al , 2020Nelson et al 2019;Yung et al 2019bYung et al , 2022Wilkins et al 2023Wilkins et al , 2022. Note that we use the SED-based SFR estimate (Section 3.5), instead of using the Hβ line.…”
mentioning
confidence: 89%